2021
DOI: 10.3390/ijerph18168683
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Protein Concentration in Healthy Older Japanese Volunteers

Abstract: The concentration of cerebrospinal fluid total protein (CSF-TP) is important for the diagnosis of neurological emergencies. Recently, some Western studies have shown that the current upper reference limit of CSF-TP is quite low for older patients. However, little is reported about the concentration of CSF-TP in the older Asian population. In this study, we retrospectively analyzed the CSF-TP concentrations in healthy older Japanese volunteers. CSF samples in 69 healthy Japanese volunteers (age range: 55–73 yea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…First, the protein extractions of the included samples were characterised. Although measured CSF protein concentrations are often lower than measured in this study (Wuschek et al, 2019;Yoshihara et al, 2021), extensive individual variability has been reported previously (Asgari et al, 2017). In order to check if there was a correlation between sample storage time and protein concentration, linear regression was performed.…”
Section:  Discussionmentioning
confidence: 78%
“…First, the protein extractions of the included samples were characterised. Although measured CSF protein concentrations are often lower than measured in this study (Wuschek et al, 2019;Yoshihara et al, 2021), extensive individual variability has been reported previously (Asgari et al, 2017). In order to check if there was a correlation between sample storage time and protein concentration, linear regression was performed.…”
Section:  Discussionmentioning
confidence: 78%